Analysis of Foam Mortar and Prefabricated Vertical Drain (PVD) Application for Soft Soil Improvement on the Aruk–Sp. Take Road Section, Sambas Regency, West Kalimantan - Victor Bela Sendoro Hia; Indrasurya B. Mochtar; Noor Endah Mochtar (Interdisciplinary Social Studies, 2025)
Infrastructure damage on the Aruk – Sp. Take Road Section, Sambas Regency (especially STA 99+000 to STA 99+550), is directly attributed to soft soil conditions characterized by low bearing capacity and high compressibility. Previous conventional repair methods were deemed ineffective, while permanent solutions involving Pile Slabs proved to be financially prohibitive for extensive road segments. This study aims to analyze the effectiveness of combining a lightweight fill material (Foam Mortar) with consolidation acceleration using Prefabricated Vertical Drains (PVD) on key geotechnical parameters: settlement, consolidation time, and slope stability. The methodology comprises soil data analysis, modeling of embankment designs with varying Foam Mortar compositions (0%, 25%, and 50%) at different heights, and consolidation calculations using a triangular PVD pattern. The analysis results demonstrate that installing PVD at an optimal spacing of 1.25 meters achieved a degree of consolidation of 91.2% within 22 weeks. Furthermore, the inclusion of Foam Mortar was proven significant in reducing the overall load and substantially improving stability. In the final height design of 3.30 meters, the 50% Foam Mortar variation reduced the maximum settlement to 1.38 meters (compared to 1.70 meters on 100% conventional earthfill) and drastically increased the Safety Factor (SF) from 1.90 to 3.06.